Search for massive supersymmetric particles decaying to many jets using the ATLAS detector in pp collisions at √s =8 TeV - Alconada Verzini, María Josefina (2015)
Results of a search for decays of massive particles to fully hadronic final states are presented. This search uses 20.3 fb-1 of data collected by the ATLAS detector in √s=8 TeV proton-proton collisions at the LHC. Signatures based on high jet multiplicities without requirements on the missing transverse momentum are used to search for R-parity-violating supersymmetric gluino pair production with subsequent decays to quarks. The analysis is performed using a requirement on the number of jets, in combination with separate requirements on the number of b-tagged jets, as well as a topological observable formed from the scalar sum of the mass values of large-radius jets in the event. Results are interpreted in the context of all possible branching ratios of direct gluino decays to various quark flavors. No significant deviation is observed from the expected Standard Model backgrounds estimated using jet counting as well as data-driven templates of the total-jet-mass spectra. Gluino pair decays to ten or more quarks via intermediate neutralinos are excluded for a gluino with mass mg<1 TeV for a neutralino mass mχ10=500 GeV. Direct gluino decays to six quarks are excluded for mg<917 GeV for light-flavor final states, and results for various flavor hypotheses are presented.